Le suicide, une pathologie carcérale ? - Laurence Guignard (Criminocorpus)
The objective of this article is to show that suicide prevention in French prisons during the second half of the 19th century comes up against a disciplinary approach that emerges in detention facilities at that time. Despite the promotion of resocialization methods and moral support for melancholic prisoners by leaders of prison reform and philanthropy such as Béranger, that disciplinary approach gives priority to measures enacted on the body. The failure of prevention, as demonstrated by prison statistics, thus appears to be inherent to the methods used: the straitjacket, security isolation cells, and the training of prison guards in techniques of resuscitation. The disciplinary system in place and particularly the depersonalization of inmates that arises from that system reflects nonetheless their juridical status. Indeed, in prison, they are no longer considered as individuals with full rights, for their identity is subjected to the defamatory character of their sentence.